Obestatin is present in saliva: alterations in obestatin and ghrelin levels of saliva and serum in ischemic heart disease - Ozbay, Yilmaz; Aydin, Suleyman; Dagli, A. Ferda; Akbulut, Mehmet; Agli, Necati L.; Kilic, Nermin; Sensoy, Dogan (Korean Society Biochemistry & Molecular Biology, 2008)
Ghrelin and obestatin are a single gene products and are a multiple functional peptides that regulates energy homeostasis, and food intake. In the present work, we studied the secretion of ghrelin and its co-secreted peptide obestatin in 44 patients with ischemic heart disease with that of 27 healthy matched controls. Here we first conducted using an immunohistochemistry assay to screen whether human salivary glands have any obestatin immunoreactivity. Then, serum and saliva obestatin and acylated ghrelin levels were determined by using Radioimmunoassay. Our immunohistochemical analysis demonstrated that obestatin was localized in the striated and excretory duct of human salivary gland. We also report for the first time that obestatin, like ghrelin, is present in human salivary gland and saliva. No evidence of the role of obestatin or ghrelin saliva levels in the context of ischemic heart disease was found. Salivary ghrelin and obestatin levels are correlated in controls with the blood levels. Determination of salivary values could represent a non-invasive alternative to serum ones that can be useful in clinical practice.
Keywords: ghrelin; ischaemic heart disease; obestatin; saliva; serum